Transformative learning theory and migration - Saskia Eschenbacher (European Journal for Research on the Education and Learning of Adults, 2020)
This paper introduces the concept of transformative conversation inspired by Arcillas concept of edifying conversation, as an extension of TL theorys notion of discourse, in the context of adult education and migration. By contrasting the idea of exchanging arguments with opening space for conversation and ones private quest for meaning and self-understanding, I introduce the idea of becoming a fellow transformative conversationalist as an appropriate attitude for promoting TL. I will (1) differentiate between an instrumental and a transformative notion of learning in the context of migration; (2) engage Rorty in a conversation with TL theory; (3) introduce Arcillas concept of edifying conversation to join and broaden the ongoing conversation and develop the concept of transformative conversation.